(3cJGH TLQI Gdjbjfs - (3SYO CHj GdMSf GdGTYQjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO bO LGA ai GdNHQ Cf Gddg JYGdi Ndb TLQI ef fhQ hdgG CQHYI CZUGf aSeGgG TLQI Gdjbjf Ke Ndb fhQ eMeO Udi Gddg Ydjg hSde ai MLGH s
(3BNQgG (B:s
(3bGd GdfHi Udi Gddg Ydjg hSde Ef Cgd GdLfg jCcdhf hjTQHhf hGdMeO ddg QH GdYGdejf GfJgi GdcJGH GdeSei HTLQI Gdjbjf HMeO Gddg hMSf Yhfg hJhajbg GdLejd s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW s
Keywords: (3GdJhMjO hGdedd hGdfMds